Feasibility, safety, and outcome of recanalization treatment in childhood stroke. Issue 6 (27th July 2018) - Bigi, Sandra; Dulcey, Andrea; Gralla, Jan; Bernasconi, Corrado; Melliger, Amber; Datta, Alexandre N.; Arnold, Marcel; Kaesmacher, Johannes; Fluss, Joel; Hackenberg, Annette; Maier, Oliver; Weber, Johannes; et al.
Abstract : Objective: Intravenous thrombolysis and endovascular therapy (IVT/EVT) are evidence‐based treatments for adults with arterial ischemic stroke (AIS). However, randomized controlled trials in pediatric patients are lacking. This study aimed to describe feasibility, safety, and outcome of IVT/EVT in children with AIS. Methods: This retrospective study (01/2000–12/2015) included a multicenter, population‐based consecutive cohort of patients aged 1 month to 16 years, diagnosed with AIS and presenting with pediatric National Institutes of Health Stroke Scale (pedNIHSS) ≥ 4. Clinical and radiological data of patients receiving IVT/EVT were compared to those receiving standard care (SC) using linear regression to adjust for potential confounders. EVT included intra‐arterial thrombolysis and/or mechanical thrombectomy. Outcome was assessed 6 months after stroke using the pediatric stroke outcome measure (PSOM). Results: Overall, 150 patients (age 7.1 ± 4.9 years, 55 [37%] females) presented with pedNIHSS ≥ 4. Recanalization treatment was performed in 16 (11%), of whom 5 (3%) were treated with IVT and 11 (7%) with EVT. Patients receiving recanalization treatment were older (mean age = 11.0 vs 6.9 years, p = 0.01) and more severely affected (median pedNIHSS = 13.5 vs 8.0, p < 0.001). Death and bleeding complications did not differ between the 2 groups. Median (interquartile range) PSOM 6 months after AIS was 2.5 (1–4.3) and 1 (0–2) in the IVT/EVT and SC groups, respectively ( p = 0.014). However, after multiple linear regression analysis, only higher baseline pedNIHSS remained associated with an unfavorable outcome ( p < 0.001). Interpretation: Recanalization treatment is feasible and seems to be safe in severely affected pediatric AIS patients. The assessment of efficacy of IVT/EVT in pediatric stroke patients requires larger studies. Ann Neurol 2018;83:1125–1132